2024
DOI: 10.1021/acscentsci.3c01518
|View full text |Cite
|
Sign up to set email alerts
|

Natural Product Synthesis in the 21st Century: Beyond the Mountain Top

Ryan A. Shenvi

Abstract: Research into natural products emerged from humanity's curiosity about the nature of matter and its role in the materia medica of diverse civilizations. Plants and fungi, in particular, supplied materials that altered behavior, perception, and well-being profoundly. Many active principles remain well-known today: strychnine, morphine, psilocybin, ephedrine. The potential to circumvent the constraints of natural supply and explore the properties of these materials led to the field of natural product synthesis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…We concur with the sentiment that "the local chemical space of a natural product can prove superior to the natural product itself." 57 Adding NP fragment-based parameterisation to enhance machine learning models and influence generative chemistry is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…We concur with the sentiment that "the local chemical space of a natural product can prove superior to the natural product itself." 57 Adding NP fragment-based parameterisation to enhance machine learning models and influence generative chemistry is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…Sir James Black, discoverer of propranolol and cimetidine, famously stated that “the most fruitful basis for the discovery of a new drug is to start with an old drug.” 56 In the genomic era, the Black principle holds ever true, as medicinal chemists, knowingly or unknowingly, are repeatedly using a small group of established NP fragments to discover clinical candidates. We concur with the sentiment that “the local chemical space of a natural product can prove superior to the natural product itself.” 57 Adding NP fragment-based parametrization to enhance machine learning models and influence generative chemistry is recommended.…”
Section: Discussionmentioning
confidence: 99%
“…The significance of natural products in pharmaceuticals cannot be overstated as over 30% of all FDA-approved new molecular entities (NMEs) are derived directly or inspired from microbial and plant species . Optimized by natural selection pressures, natural products are refined to have optimal interactions with biological macromolecules, membrane permeability, biomolecular compatibility, and stability, thus sharing key properties of drug likeness. , A recent analysis revealed that over 80% of CNS agents are derived directly or inspired from natural products, and the scaffolds of just 20 natural products yielded more than 400 clinically approved CNS drugs …”
Section: Introductionmentioning
confidence: 99%